Enhancing Arabic Learning Outcomes Through the Course Review Horay Cooperative Learning Model - Nurisnaini, Fitriana; Amrulloh, Muhammad Afif; Nurwahidin, Diki (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
A well-designed evaluation process can increase student motivation and strengthen understanding of the material taught, thus achieving more optimal learning outcomes. The researcher intends to analyze the effect of course review horay type cooperative learning model in improving students' Arabic learning outcomes. This study used a quantitative approach, specifically an experiment with a pre-experiment design. The study involved 16 students in class IVB SDIT Subulussalam who were assessed using observation sheets and written tests. The results showed that students were very active and engaged during the learning process, with a success rate of 61% - 100% in terms of activeness. Hypothesis testing confirmed that the independent variable (cooperative learning model) significantly influenced the dependent variable (students' Arabic learning outcomes). This supports the initial hypothesis and shows that cooperative learning models positively impact student engagement and enthusiasm. These findings have important implications for educational practice, as these models can contribute to more effective learning experiences and outcomes.